Extracorporeal Membrane Oxygenation in Miliary Tuberculosis and AIDS: A Case Report - Frick, Sonia Erika; Flothmann, Christoph; Preiswerk, Benjamin; Behr, Renate; Genoni, Michele (The Thoracic and Cardiovascular Surgeon Reports, 2015)
Background The aim of this study is to present the success of a multidisciplinary approach in a patient with a rare triad of disease.Case Description A 33-year-old patient with newly diagnosed human immunodeficiency virus infection presented with miliary tuberculosis, consecutive adult respiratory distress syndrome, and multiple-organ failure. An interdisciplinary, time-limited approach combining extracorporeal membrane oxygenation, intensive care therapy, hemodiafiltration, tuberculostatic therapy, steroids, and antiretroviral therapy led to survival despite a low probability at presentation.Conclusion Even though the use of such extensive and expensive treatment can be questioned, this example encourages an aggressive approach in a young patient, even in situations of multiple diagnosis of individually limited prognosis.
Keywords: adult respiratory distress syndrome; human immunodeficiency virus; miliary tuberculosis; extracorporeal membrane oxygenation